Observation of force-detected nuclear magnetic resonance in a homogeneous field - Madsen, L. A. (National Academy of Sciences, 2004)
We report the experimental realization of BOOMERANG (better observation of magnetization, enhanced resolution, and no gradient), a sensitive and general method of magnetic resonance. The prototype millimeter-scale NMR spectrometer shows signal and noise levels in agreement with the design principles. We present (1)H and (19)F NMR in both solid and liquid samples, including time-domain Fourier transform NMR spectroscopy, multiple-pulse echoes, and heteronuclear J spectroscopy. By measuring a (1)H-(19)F J coupling, this last experiment accomplishes chemically specific spectroscopy with force-detected NMR. In BOOMERANG, an assembly of permanent magnets provides a homogeneous field throughout the sample, while a harmonically suspended part of the assembly, a detector, is mechanically driven by spin-dependent forces. By placing the sample in a homogeneous field, signal dephasing by diffusion in a field gradient is made negligible, enabling application to liquids, in contrast to other force-detection methods. The design appears readily scalable to μm-scale samples where it should have sensitivity advantages over inductive detection with microcoils and where it holds great promise for application of magnetic resonance in biology, chemistry, physics, and surface science. We briefly discuss extensions of the BOOMERANG method to the μm and nm scales.